On the heterophase liquid thermodynamics and cooperative dynamics - Bakai, O.S. (Condensed Matter Physics, 2010)
The thermodynamics and cooperative dynamics of heterophase liquid states is considered taking into account frustration and volumetric interaction of the solid-like fluctuons. It is found that the glass transition temperature range is scaled by difference of the frustration parameter and mean energy of the volumetric interaction. A model of the cooperative relaxation with finite cooperatively rearranging domains is considered. The fictitious Kauzmann and Vogel-Fulcher temperatures are determined. It is found that they are close to a proper accuracy. Correlation of the temperatures of glass transition, Vogel-Fulcher and "ideal" glass transition (as it is determined in the mode coupling model) is considered too. Розглянуто термодинаміку та кооперативну динаміку гетерофазної рідини з урахуванням фрустрації й об'ємної взаємодії твердотільних флуктуонів. Установлено, що ширина температурного інтервалу перетворення рідини в скло є пропорційною різниці параметра фрустрації та енергії об'ємної взаємодії. Знайдено уявні температури Кауцмана і Фогеля - Фулчера. Вони виявились близькими з гарною точністю. Розглянуто кореляцію температури склування, Фогеля - Фулчера та температури "ідеального" перетворення рідина - скло, яке описано в моделі взаємодіючих мод.